Participation Right Fulfillment in Early Childhood Education through Educative Game Tools - Senowarsito Senowarsito; Siti Musarokah (Intelektual Pustaka Media Utama, 2018)
The research aims at describing the implementation of participation rights in early childhood education through educative game tools (Alat Permainan Edukatif: APE) and finding out the problems encountered by the teachers in implementing participation rights through APE. The research type is qualitative research. The subjects of the research were four teachers of early childhood education in Semarang Municipality including play group and kindergarten school which were selected by using purposive sampling. The data were collected by field observation and depth-interview and analyzed in the form of a descriptive qualitative analysis. The results show that some APEs implemented in early childhood education were potentially able to enhance participation rights, but the teachers were not aware on this aspect. They tended to focus on the academic outputs and on fulfilling joyful learning. The main factor was the teachers’ knowledge on the importance of APE for comprehending the participation rights of the child in learning process, including the limited number of APEs created and the flexibility of the APEs available. As participation rights are essential in learner-centered approach, APE as an educational game tool should be created and manipulated to accommodate the rights, including protection and provision rights.